2021
DOI: 10.3390/vaccines9111350
|View full text |Cite
|
Sign up to set email alerts
|

ISCOM-like Nanoparticles Formulated with Quillaja brasiliensis Saponins Are Promising Adjuvants for Seasonal Influenza Vaccines

Abstract: Vaccination is the most effective public health intervention to prevent influenza infections, which are responsible for an important burden of respiratory illnesses and deaths each year. Currently, licensed influenza vaccines are mostly split inactivated, although in order to achieve higher efficacy rates, some influenza vaccines contain adjuvants. Although split-inactivated vaccines induce mostly humoral responses, tailoring mucosal and cellular immune responses is crucial for preventing influenza infections.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…40 nm size, and obtained a combination of antigens, cholesterol, phospholipid and the Quillaja saponaria saponin. This combination results in a hydrophobic interaction between the lipids and the antigen [ 138 ].…”
Section: Adjuvants and Formulationmentioning
confidence: 99%
“…40 nm size, and obtained a combination of antigens, cholesterol, phospholipid and the Quillaja saponaria saponin. This combination results in a hydrophobic interaction between the lipids and the antigen [ 138 ].…”
Section: Adjuvants and Formulationmentioning
confidence: 99%
“…ISCOMs-based vaccines containing influenza virus, Mycobacterium tuberculosis , RSV, and measles antigen have been indicated to effectively induce an immune response in the body after nasal/pulmonary vaccination, producing high titers of IgA in the nasal cavity and the lung [ 197 , 198 , 199 , 200 , 201 , 202 , 203 ]. In certain cases, this local mucosal inoculation produces greater immunity compared to that produced upon injectable vaccination.…”
Section: Nasal Vaccine Adjuvantsmentioning
confidence: 99%
“…Over the last decade, our research team has been studying saponins extracted from the leaves of Quillaja brasiliensis (QB) as an alternative to saponins extracted from Quillaja saponaria tree bark ( 9 , 20 23 ). Comprehensive chemical characterization has shown that the two species share a myriad of saponin structures, including well-known saponins with high immunoadjuvant activity, as well as QS-21 ( 12 , 21 , 24 ), a potent adjuvant isolated from the Q. saponaria tree and which is currently used in a few licensed vaccines ( 8 , 10 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive chemical characterization has shown that the two species share a myriad of saponin structures, including well-known saponins with high immunoadjuvant activity, as well as QS-21 ( 12 , 21 , 24 ), a potent adjuvant isolated from the Q. saponaria tree and which is currently used in a few licensed vaccines ( 8 , 10 , 25 ). Furthermore, several studies have shown the immunoadjuvant potential of saponins from QB and their ability to form ISCOM-like nanostructures ( 9 , 11 , 21 , 22 , 26 ). Thus, leaves of QB are a readily renewable source of these important secondary metabolites of high added value and of relevant importance for public health ( 9 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation